EKSTRAKSI ACETOGENIN DARI DAUN DAN BIJI SIRSAK (Annona muricata L) DENGAN PELARUT ASETON (Jurnal Teknik Kimia USU, 2016)
Annona muricata L contain bioactive compounds acetogenins. Acetogenins which was synthesized through reaction between polyketide derived-acetic acid with 35-39 carbon atom in fatty acid, is the secondary metabolite of Annonaceae plant. This research aims to determine the variable that influence in leaf and Annona muricata seed extraction so that high yield value can be obtained and to prove the presence of acetogenins compound qualitatively. The materials used are Annona muricata leaves, Annona muricata seeds and aceton. The changing variables in this research is the mass of the samples for Annona muricata leaves powder that are 15 g, 25 g, 35 g and Annona muricata seeds powder that are 10 g, 20 g, 30 g which the extraction time are 30 minutes, 40 minutes, 50 minutes and 60 minutes. This research divided into two steps. The first step is the extraction of Annona muricata leaves and Annona muricata seeds using soxhletation method with 250 mL acetone for Annona muricata leaves, 200 mL aceton for Annona muricata seeds and extraction temperature is ± 58 oC. The second step is purification of the extract using distillation process. In this research, the highest yield value extract of Annona muricata leaves obtained is 55,33% with 15g mass of sample and 60 minutes for the extraction time. The highest yield value extract of Annona muricata seeds obtained is 62 % with 10 g mass of sample and 40 minutes for the extraction time. FTIR analysis showed the presence of functional groups such as lactone, THF, hyrdroxyl and aliphatic chains which indicates acetogenins compound’s presence.